GAMBARAN GANGGUAN MUSKULOSKELETAL PENGGUNAAN SEPATU HIGH HEELS PADA SALES PROMOTION GIRL (SPG) TRANSMART CILANDAK - Margareth Helenda Natalia Tambun, (2022)
In today's modern era, many women choose life to be career women. This is not unfamiliar to society. Some career women who are pursued are required to use high heels in accordance with the SOP where they work. This is done so that women look beautiful, elegant, and attractive. The use of high heels on the heel will make the foot tiptoe with a standing position all the time long enough and use high heels as high heels as high as 3-5 Cm which will cause pain in the muscles (MSDs). The main goal in this study was to find out the Picture of Musculoskeletal Disorders of High Heels Use In Sales Promotion Girl (SPG) Transmart Cilandak. The method used by the author is descriptive with a cross sectional study approach with the number of sample respondents n = 32. The research instrument used the Nordic Musculoskeletal Questionare (NMQ) and Numeric Pain Rating Scale (NPRS) questionnaires. The results in the study showed in 32 respondents complained of musculoskeletal dominant in the ankle regio with a large percentage (75%). And the level of pain when moving is mild pain (1-3) with a percentage (43.8%), then pain when still mild pain (1-3) with a percentage (37.5%), and pain when pressed that is mild pain (1-3) large percentage (65.6%). From the results of this study, it can be concluded that there is a Musculoskeletal Disorder in the Lower extremity area of the Cilandak Transmart SPG.